Do Personal Traits, Creativity and Organizational Trust Influence the Innovative Skills of Technical Students an Evidence from a Private University? - Shiva H. C. Prasad; Kamath Giridhar; Gopalakrishna Barkur; Nora Kiefer (International Journal of Entrepreneurship, 2018)
Technical course students adopt methodical, rational strategies for Engineering Problem Solving (EPS) skills as their curriculum are ingrained with analytical thinking abilities in solving the problems in an innovative way. Thus, innovative skills are determined by personal traits such as self-confidence, self-determination, risk-taking, tolerance of ambiguity, the achievement motive of a person, creativity and trust in the organization. This empirical research identifies the relationship between innovative skills of technical students by developing a causal model that measures their personal traits, creativity and the trust in the organization. The methodology adopted is a survey data from technical course students in a Private University, India. The printed questionnaire was administered to students and their responses are analyzed. The findings of this research study reveal that the personal traits of self-confidence and risk-taking have a significant influence on the innovative skills but lack of organizational trust does not support. The significance of this research recommends that Private University incubation center must plan to develop awareness, conduct workshops on creativity and thus build a strong organizational trust in students, to enhance the innovative skills.
Keywords: L26; M2; 330; Creativity; Innovative Skills; Organizational Trust; Personal Traits; Technical Students